2022
DOI: 10.1097/gox.0000000000004010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Efficacy of Two Regional Pain Management Modalities in Autologous Breast Reconstruction

Abstract: Background: At our institution, multimodal opiate-sparing pain management is the cornerstone of our enhanced recovery program for autologous breast reconstruction. The purpose of this study was to compare postoperative outcomes and pain control metrics following implementation of an enhanced recovery program with two different regional analgesia approaches. Methods: This retrospective cohort study identified 145 women who underwent autologous breast reconstruction from 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…27 Some, but not all, previous studies reported significantly shorter length of stay for patients receiving liposomal bupivacaine via a TAP block for DIEP flap reconstruction specifically. 15,16,[21][22][23] Other studies assessing costs with liposomal bupivacaine via TAP block versus comparators in DIEP flap reconstruction have not observed substantial cost differences between groups. 21,22 Although previous breast reconstruction studies reported reduction in inpatient opioid consumption with liposomal bupivacaine, some showed no evidence of significant reduction, and how liposomal bupivacaine affected other outcomes (including postdischarge outcomes) after DIEP flap procedures is less clear.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…27 Some, but not all, previous studies reported significantly shorter length of stay for patients receiving liposomal bupivacaine via a TAP block for DIEP flap reconstruction specifically. 15,16,[21][22][23] Other studies assessing costs with liposomal bupivacaine via TAP block versus comparators in DIEP flap reconstruction have not observed substantial cost differences between groups. 21,22 Although previous breast reconstruction studies reported reduction in inpatient opioid consumption with liposomal bupivacaine, some showed no evidence of significant reduction, and how liposomal bupivacaine affected other outcomes (including postdischarge outcomes) after DIEP flap procedures is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…20 In this systematic review, liposomal bupivacaine, a formulation of the local anesthetic bupivacaine enabling controlled release of bupivacaine for prolonged analgesia, was highlighted for pain management after breast reconstruction. 20 Previous studies investigated liposomal bupivacaine administered as a TAP block (including as part of an ERP protocol) for DIEP flap breast reconstruction, [15][16][17][21][22][23] with some showing reduced opioid consumption versus historical controls. 15,23 Prior studies of DIEP flap procedures found that liposomal bupivacaine was associated with lower opioid use compared with bupivacaine administered via TAP blocks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations